Pakeliran Sampakan “Sang Panggung” - Sindhunata Gesit Widiharto; Trisno Santoso (Gelar : Jurnal Seni Budaya, 2021)
The combination of puppetry and theater creates an alternative offering a new style of treatment in the form of contemporary theater called “Pakeliran Sampakan”. Pakeliran sampakan carries the mission of modernizing traditional art with the hope of being able to answer the public's saturation regarding spectacle that smells Indonesian culture, especially wayang kulit with the target market the young people. “Sang Panggung” is an adaptation of a story from “Nyi Panggung” written by Eko Tunas which tells about the life behind the scenes of the group of tobong Ketoprak Eka Mardhika. The results of the work represent the form of performances by the tobong ketoprak artists, with the story "Sang Panggung". Like the marginalized who are alienated because of their deposed honour by the outside culture, it needs an action by doing 'transmigration'. It doesn’t only mean moving from one island to another but also a change in the human mindset to be renewed towards the sophisticated technology of mass media, in order that traditional arts can always involve in the international competitions.